Finding a Place: Education in the Meiji Period and Doshisha University - Derrah, Richard H. (Advances in Social Sciences Research Journal, 2024)
This paper details the founding of Doshisha University by Joseph Hardy Niijima. It describes the unique social role played by the university and then contextualizes this role within the broader narrative of the creation of a modern educational system during the Meiji Period. The findings indicate that the combination of Christian and science education helped former samurai who felt disenfranchised within the new modern era of Japan to find their place within this new society.